2017
DOI: 10.1515/acve-2017-0002
|View full text |Cite
|
Sign up to set email alerts
|

Viral molecular and pathological investigations ofCanid herpesvirus1 infection associated respiratory disease and acute death in dogs

Abstract: Canid herpesvirus 1 (CaHV-1) is a member of the canine infectious respiratory disease complex (CIRDC). The outcome of CaHV-1 infection can be occasionally fatal. So far, no information on CaHV-1 circulation in Thailand has been reported resulting in a lack of preventive strategies. In this study, nasal (NS) and oropharyngeal (OS) swabs were collected from 100 live dogs with respiratory distress. Among them, 23 pleural effusions were aspirated. A panel of CIRDC-associated viruses was screened by (RT)-PCR, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
(42 reference statements)
2
6
0
Order By: Relevance
“…Our finding is similar to other studies in which there was no statistical difference between age and detection of CHV-1 [7,14,19,21]. In contrast to our findings, other researchers indicated that the rate of the infection was significantly higher in older dogs compared with younger ones [16,25,28].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our finding is similar to other studies in which there was no statistical difference between age and detection of CHV-1 [7,14,19,21]. In contrast to our findings, other researchers indicated that the rate of the infection was significantly higher in older dogs compared with younger ones [16,25,28].…”
Section: Discussionsupporting
confidence: 89%
“…(2015) performed in Denmark, 13 out of 57 (22.8%) dead puppies were positive for CHV-1 infections by real-time PCR (qPCR) while histopathological and in situ hybridization results were inconsistent [23]. Moreover, CHV-1 was defined as a respiratory virus and detected in nasal swabs of dogs via PCR 6 [24,25]. Adult dogs also can be implicated in spread of infections.…”
Section: Discussionmentioning
confidence: 99%
“…Another study performed in Denmark by Larsen et al (2015) presented that CHV-1 was found in 22.8% of tissue pools of the dead puppies using real-time PCR (qPCR), however histopathological and in situ hybridization findings were inconsistent [24]. Moreover, CHV-1 infection associated with respiratory diseases was detected in 32 out of 100 nasal and oropharyngeal swabs of dogs and 6 out of 32 pleural effusions using multiplex PCR in Thailand [14]. In another study conducted in Brazil, CHV-1, as a respiratory virus, was found in 6% of the nasal secretions of shelter dogs via PCR [25].…”
Section: Discussionmentioning
confidence: 99%
“…The virus is responsible for fetal death, abortion, mummification, or stillbirth in pregnant bitches [11]. Moreover, respiratory disease, ocular signs, and genital lesions are also documented [5, [12][13][14]. Lifelong latent infection is associated with localization of CHV-1 to nerve ganglia following recovery [1].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, canine bocavirus [13, 14], canine hepacivirus [15] and canine circovirus [16] have been detected in respiratory tract samples of dogs showing respiratory illness, but the pathogenic roles of those viruses are poorly determined. Although new viruses have emerged, the common CIRDVs are still important contributors to respiratory disease [17, 18]. Additionally, current core vaccines that are routinely used in dogs prevent some CIRDVs, such as CPIV, CDV, and CAdV-2, but not CaHV-1, CRCoV and CIV.…”
Section: Introductionmentioning
confidence: 99%